Vocationalization of Higher Education in Japan - Yoshinaga, Keiichiro (International Higher Education, 2024)
<h3 id="as-it-enters-the-universal-stage-japanese-higher-education-is-experiencing-a-series-of-changes-one-is-the-replacement-of-academic-subjects-with-vocational-ones-another-is-the-shift-from-written-entrance-examinations-to-portfolio-selection-and-the-third-is-the-rise-of-professional-management-instead-of-faculty-control-these-changes-accelerated-by-the-demand-for-international-students-due-to-declining-domestic-student-numbers-challenge-traditional-ideas-about-higher-education" data-pm-slice="1 1 []">As it enters the universal stage, Japanese higher education is experiencing a series of changes. One is the replacement of academic subjects with vocational ones, another is the shift from written entrance examinations to portfolio selection, and the third is the rise of professional management instead of faculty control. These changes, accelerated by the demand for international students due to declining domestic student numbers, challenge traditional ideas about higher education.